Synthesis of zirconium modified FDU-12 by different methods and its application in dibenzothiophene hydrodesulfurization. Issue 48 (2nd August 2018) - Meng, Qian; Du, Peng; Wang, Bo; Duan, Aijun; Xu, Chunming; Zhao, Zhen; Liu, Cong; Hu, Di; Li, Yuyang; Xiao, Chengkun
Abstract : Zirconium modified mesoporous materials were successfully synthesized by different methods including direct synthesis and post synthesis (grafting and impregnating). Abstract : Zirconium modified mesoporous materials were successfully synthesized by different methods including direct synthesis and post synthesis (grafting and impregnating). Meanwhile, the corresponding catalysts were prepared. A series of techniques, including small-angle X-ray scattering (SAXS), transmission electron microscopy (TEM) and pyridine adsorption Fourier-transform infrared (Py-IR), were used to characterize the properties of supports and catalysts. The results of SASX and TEM characterization proved that all the modified materials retained the well-ordered mesoporous structure from the FDU-12 material. N2 adsorption–desorption results showed that the Zr-FDU-12 material obtained by direct synthesis (Zr-in-F) possessed higher specific surface area (709 m 2 g −1 ), pore volume (0.65 cm 3 g −1 ) and larger pore size (18.7 nm) than the Zr-FDU-12 materials obtained by the post synthesis. According to the characterization result of UV-Vis, Zr-in-F exhibited better dispersion of Zr species than materials obtained by the post synthesis. It was found that the incorporation of Zr species not only increased acidities but also enhanced the sulfidities of the Mo species. All the catalysts were evaluated for their activities in the hydrodesulfurization of dibenzothiophene, and the NiMo/Zr-in-F catalyst exhibited the best catalytic performance (97.3%), attributed to its higher specific surface area, larger pore size, higher sulfidity, and more acidic sites.